1988
DOI: 10.1073/pnas.85.19.7129
|View full text |Cite
|
Sign up to set email alerts
|

Chemical synthesis and enzymatic activity of a 99-residue peptide with a sequence proposed for the human immunodeficiency virus protease.

Abstract: Retroviral proteins, including those from the human immunodeficiency virus (HIV), are synthesized as polyprotein precursors that require proteolytic cleavage to yield the mature viral proteins. A 99-residue polypeptide, encoded by the 5' end of the pol gene, has been proposed as the processing protease of HIV. The chemical synthesis of the 99-residue peptide was carried out by the solid-phase method, and the isolated product was found to exhibit specific proteolytic activity upon folding under reducing conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(29 citation statements)
references
References 29 publications
1
28
0
Order By: Relevance
“…HIV-1 protease belongs to the mechanistic class of aspartic proteases (3)(4)(5)(6)(7)(8)(9). Earlier studies with other members of this family, such as human renin or pepsin, showed that synthetic peptidomimetic compounds containing a hydroxyethylene isosteric insert as a nonhydrolyzable synthetic replacement of the Pj-Pt scissile amide bond are able to inhibit the catalytic function of such proteases (25,26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HIV-1 protease belongs to the mechanistic class of aspartic proteases (3)(4)(5)(6)(7)(8)(9). Earlier studies with other members of this family, such as human renin or pepsin, showed that synthetic peptidomimetic compounds containing a hydroxyethylene isosteric insert as a nonhydrolyzable synthetic replacement of the Pj-Pt scissile amide bond are able to inhibit the catalytic function of such proteases (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…One attractive target for specific anti-viral therapy is the protease, encoded by the pol gene of HIV (1,2). This aspartic protease (3)(4)(5)(6)(7)(8)(9) cleaves the viral p55 gag precursor into the four structural proteins of the virion core (p17, p24, p8, and p7); additionally, protease activity is required for cleavage of the p160 gag-pol precursor, which yields protease itself, reverse transcriptase (RT), and endonuclease as well as structural proteins (10). Such processing of the HIV gag and gag-pol precursor polyproteins is essential for the maturation of infectious virions (11)(12)(13)(14).…”
mentioning
confidence: 99%
“…However, the genome is gene-rich, containing nine open reading frames (ORFs) that produce 15 proteins, 11 of which are essential for viral replication. Furthermore, the final gene products from the gag, pol, and env genes are produced via proteolytic cleavage of a polyprotein (128), which means that a deletion or frameshift upstream may disrupt all downstream proteins within the polyprotein. Thus, mutation of a single target could knock out the function of several proteins at once.…”
Section: Human Immunodeficiency Virusmentioning
confidence: 99%
“…Therefore, production and purification of large quantities of this enzyme are prerequisites for the development of assays which allow the identification of potent and selective inhibitors. Several laboratories have described the production of HIV-1 protease either by expression in Escherichia coli or Saccharomyces cerevisiae [5 15] or by the chemical synthesis of the 99 amino acids-long monomer [14,16,17].…”
Section: Introductionmentioning
confidence: 99%